Pengaruh Model Pembelajaran Contextual Teaching Learning Terhadap Hasil Belajar Siswa Pada Pembelajaran Sutema 1 Hewan Dan Tumbuhan Di Lingkungan Rumahku Kelas IV SD Negeri 091273 Karang Bangun - Rantika Sinaga; Rio Parsaoran Napitupulu; Hetdi Sitio (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research is based on the low thematic student learning outcomes at SD Negeri 091273 Karang Bangun, this can be seen from the student learning outcomes in thematic learning which are still relatively low or below the minimum completeness criteria (KKM) standards. The aim of this research is to find out the significant differences between students' learning outcomes using the contextual teaching learning model and student learning outcomes in subtheme 1 animals and plants in my home environment. Calculation results with SPSS version 21 using obtained results. This is measured from the results of the average student score which was originally 38.54 and after implementing the contextual teaching learning model it rose to 89.49. the results of the hypothesis test show that from the results of the normality test of the experimental data, a significant Kolmogorov-Smirnov value of 0.200 is obtained, which means it has a normal distribution. Homogeneity test, obtained a significant value of 0.924, which means homogeneous. t-test obtained tcount of 14.497 which was then compared with ttable of 2.073 with a significance level of 5%. The difference is said to be significant if tcount > ttable. If tcount > ttable then HO is rejected and Ha is accepted, and if tcount < ttable then Ho is accepted and Ha is rejected. it turns out tcount > ttable (14.497 > 2.073) so it can be stated that the score has increased significantly in student learning outcomes so that Ha learning outcomes are accepted. This means that there is an influence of the contextual teaching learning model on student learning outcomes in learning subtheme 1 animals and plants in my home environment, class IV of SD Negeri 091273 Karang Bangun.